'And Eden from the Chaos rose': utopian order and rebellion in the Oxford Physick Garden. Issue 2 (3rd April 2019) - Svensson, Anna
ABSTRACT: Abel Evans's poem Vertumnus (1713) celebrates Jacob Bobart the Younger, second keeper of the Oxford Physick Garden (now the Oxford University Botanic Garden), as a model monarch to his botanical subjects. This paper takes Vertumnus as a point of departure from which to explore the early history of the Physick Garden (founded 1621), situating botanical collections and collecting spaces within utopian visions and projects as well as debates about order more widely in the turbulent seventeenth-century. Three perspectives on the Physick Garden as an ordered collection are explored: the architecture of the quadripartite Garden, with particular attention to the iconography of the Danby Gate; the particular challenges involved in managing living collections, whose survival depends on the spatial order regulating the microclimates in which they grow; and the taxonomic ordering associated with the hortus siccus collections. A final section on the ideal 'Botanick throne' focuses on the metaphor of the state as a garden in the period, as human and botanical subjects resist being order and can rebel, but also respond to right rule and wise cultivation. However, the political metaphor is Evans's; there is little to suggest that Bobart himself was driven by utopian, theological and political visions.